2014
DOI: 10.1159/000370232
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of KELnull Phenotype in Brazilians

Abstract: Background: KELnull (K₀) persons can produce clinically significant anti-KEL5 antibody after transfusion and/or pregnancy, requiring K₀ blood transfusion when indicated. 37 K₀ alleles have been reported in studies over different populations, but none in Amerindian-Caucasian descendants from South America. The aim of this study was to identify the molecular basis of K₀ phenotype in Brazilians. Methods: We investigated three K₀ samples from different Brazilian blood banks (Recife, Manaus, and Vila Velha) in wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In the present study, three KEL*02N alleles were identified: c.1546C>T ( KEL*02N.17 ), c.382C>T ( KEL*02N.26 ), and c.1042 C>T ( KEL*02N.04 ). Of these, KEL*02N.26 has been described among Native Americans and people of African ancestry and KEL*02N.04 among Caucasians, Portuguese, and Brazilians 15,17,47,48 . Therefore, the presence of these altered alleles in the studied patient population was expected.…”
Section: Discussionmentioning
confidence: 91%
“…In the present study, three KEL*02N alleles were identified: c.1546C>T ( KEL*02N.17 ), c.382C>T ( KEL*02N.26 ), and c.1042 C>T ( KEL*02N.04 ). Of these, KEL*02N.26 has been described among Native Americans and people of African ancestry and KEL*02N.04 among Caucasians, Portuguese, and Brazilians 15,17,47,48 . Therefore, the presence of these altered alleles in the studied patient population was expected.…”
Section: Discussionmentioning
confidence: 91%
“…While, K+ k-individuals still express other Kell antigens, e.g. Kp b or KEL11, none of the Kell antigens are expressed on cells of the Kell-null phenotype, K 0 , which arise from homozygous or compound heterozygous KEL-inactivating mutations [6][7][8]. K 0 individuals are exceedingly rare and may only be found at frequency fewer than 1 individual per 1 million Austrians [6].…”
Section: Introductionmentioning
confidence: 99%
“…They also included samples from individuals with a K 0 phenotype and a sample from an individual with McLeod syndrome, in which Kell antigens are weakly expressed. In a Brazilian study, three K 0 samples were confirmed by flow cytometry to be K−, k−Kp(a−b−), Jsb− .…”
Section: Detection and Semiquantification Of Erythrocyte Antigensmentioning
confidence: 94%